DIGITAL TRANSFORMATION AND COVID-19: EXPERIENCE AND PROSPECTS OF SMART SOCIETY DEVELOPMENT IN JAPAN (Journal of Oriental Studies, 2026)
Due to the rapidly changing civilizational landscape of the world, the need for the evolution of modern society is increasing manifold, and Japan is the country where the new-style humanity is being formed at an unprecedented pace. Objective: to consider the peculiarities of the creation and development of Society 5.0 in the context of analysing the implementation of this direction in Japanese practice by summarizing the main components of the sphere. The main methods were the method of system analysis, using which the key components of digitalization of modern society in Japan were studied, and the historical method, using which the peculiarities of the introduction of information technology in all spheres of life of the country and society were summarized. The paper examined the basic semantic elements of such a phenomenon as “digital society” – designations, terms, characteristic features, common features, and distinguishing factors. It was recorded that the increased indicators of modern humanity in the early XXI century have ceased to fully satisfy its needs and demands, and, in connection with this circumstance, there is a need to create a new form of society – the symbiosis of man and digital technologies. In the context of the ethical side of the issue, social and cultural problems arise, namely, how the synergetic combination of the living organism and robotic elements will affect Japanese society in the future. During the period of pandemic restrictions in Japan, the “digital society”, the foundation of which was laid at the beginning of the twenty-first century, began to take shape. Due to the growing level of social and interpersonal isolation of Japanese citizens, such elements as the virtualization of public communications began to emerge in the environment of public communication, namely, the growing demand for online medical services, the popularity of online education, and the transfer of all traditional forms of communication to social networks. Through the prism of using the experience of digitalization of social, political, and other spheres of interaction in Japan, it is summarized that in Kazakhstan, there are all the prerequisites for its successful application in national practice. The results and conclusions of the work can be used as a practical basis for future scientific research, as well as in the context of developing strategies for state and social development in the coming years.Keywords: Japan, Society 5.0, artificial intelligence, Internet of things, depopulation, robotics, pandemic.